Tingkat Parasitisasi dan Deskripsi Parasitoid yang Memarasit Aphis gossypii (Glover) (Hemiptera: Aphididae) Asal Agroekosistem Dataran Rendah dan Dataran Tinggi Sumatera Selatan - Riyanto Riyanto; Siti Herlinda; Abu Umayah; Chandra Irsan (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The parasitic level research and description of the parasitoid species which were parasitic towards Aphis gossypii (Glover) (Hemiptera : Aphididae ) origin the agroecosystem of the lowland and highland of South Sumatra has not been reported, although this information is needed as a foundation of biological control of A. gossypii in South Sumatra. The purpose of this study was to determine the parasitic level and provide information about the description of the parasitoid which were parasitic towards A. gossypii origin the agroecosystem of the lowland and highland of South Sumatra. Survey and exploration the parasitoid which were parasitic towards A. gossypii conducted at 11 sites in South Sumatra vegetable center.Â The identification of parasitoid species was conducted in the laboratory of Entomology Department of the Faculty of Agriculture University of Sriwijaya. The results showed the parasitic level of Aphidius sp. and Diaeretiella rapae was higher during the dry season in both lowland and highland compared to the parasitic level of Aphelinus sp. However, Aphelinus sp. could only spread in the lowland. The main characteristics of Aphidius sp. (Aphidiidae) has shaped antennae filiform and segmented 13. The front wings have a triangular pterostigma. D. rapae, (Aphidiidae) has shaped antennae filiform and segmented 14. The front wings has a triangular pterostigma. The hind wing has a perfect basal cells. Aphelinus sp. (Aphelinidae) has an shaped goblets antennae and eight segmented and the last segments three of the antennae enlarged or club. Marginal venation long wings, while the venation postmarginal and stigma reduction. In addition there are two species of hyperparasitoid which were found to be parasitic towards parasitoid A. gossypii, were Ooencyrtus sp. and Aphiidencyrtus sp. (Encyrtidae) especially in the lowland.